Relationship between ferritin and maternal hemoglobin levels with those of newborns in a public hospital in Lima, Peru - Cabello Morales, Emilio Andrés (2024)
Objective: To evaluate the relationship between maternal FS and Hb levels with the FS and Hb levels of their newborns. Material and methods: Correlational study. It included pregnant women at term, without complications, and newborns with normal delivery. Chronic diseases, infections, hemoglobinopathies were excluded; Low weight and prematurity NB. A sample was estimated at 95% confidence and 90% statistical power. The pregnant women were recruited consecutively. FS was determined by chemiluminescence and Hb by impedance in maternal venous blood and umbilical cord. Maternal anemia was considered: Hb<11g/dl, maternal DH: FS<30ng/ml. Descriptive statistics, Pearson or Spearman (r), Student T and Wilcoxon Rank Sum test were performed. p<0.05 was considered significant. Results: We included 74 pregnant women and NB. Maternal age was 26 years (IQR:22-31), gestational age 39.06±1.0 weeks. Maternal anemia was found in 36.4% (mild or moderate in 96.3%), Hb ≥9g/dl in 94.6% and HD in 67.6%. No newborn presented DH or anemia. The overall correlation between FS and maternal and newborn Hb was non-significant. With maternal FS <30ng/ml the correlation was significant (r=0.339; p=0.01). No significant difference was found between the anthropometric characteristics of the newborn of anemic versus non-anemic mothers. Conclusions: No significant correlations were found for FS or maternal Hb with FS and Hb of their NBs, however, with a maternal FS cut-off point <30ng/ml, the correlation was significant. It is worth validating this FS cut-off point for use in the diagnosis and monitoring of DH during pregnancy. Keywords (MeSH/NLM): Pregnant women, infant newborn, ferritins, hemoglobins.